Особливості перспектив використання безбатарейних джерел додаткового живлення для мікропроцесорних пристроїв із інтегрованими GSM/GPS/GPRS модулями - Цехмістро, Р. І.; Шаповалов, С. В.; Першин, Є. В. (ХНУРЕ, 2022)
The given work is devoted to a comparative analysis of devices that provide power to microprocessor devices without the use of a traditional autonomous battery source. A detailed description of the converter of mechanical energy into electrical with the possibility of accumulating the converted energy is given. Built-in inexpensive GSM/GPS/GPRS modules used by civilians with an estimate of power consumption and a method for obtaining energy by piezoelectric transformation of mechanical energy are described.